Case report: Diagnosis of apical hypertrophic cardiomyopathy that escaped clinical and echocardiographic investigations for twenty years: Reasons and clinical implications - Caiati, Carlo; Stanca, Alessandro; Lepera, Mario Erminio (Frontiers in Cardiovascular Medicine, 2023)
Background Apical hypertrophic cardiomyopathy (ApHCM) is a rare form of hypertrophic cardiomyopathy which predominantly affects the apex of the left ventricle. The diagnosis can be challenging due to several factors, ranging from no typical clinical and electrocardiogram (EKG) findings to potential difficulties in executing and interpreting the echocardiographic examination. Case presentation We report the case of an 84-year-old woman who came to our echo-lab to undergo a routine echocardiogram. She had a history of permanent atrial fibrillation, paced rhythm and previous episodes of heart failure (HF), allegedly explained by a diagnosis of hypertensive heart disease that had been confirmed many times over the previous 20 years. The clinical examination and the EKG were unremarkable. The echocardiographic images were poor quality. But a senior cardiologist, expert in imaging and echocardiography, noted the lack of delineation of the endocardial border of the left ventricular (LV) apex region. Contrast echocardiography was performed and severe apical hypertrophy discovered. Conclusion ApHCM can be a challenging diagnosis. Contrast echocardiography must always be applied in cases of poor delineation of the LV apical endocardial border at baseline echocardiography. Timely detection and appropriate lifestyle intervention might slow the development of LV hypertrophy, and possibly minimize and delay heart failure (HF) related symptoms and arrhythmias. The prognosis remains relatively benign during long term follow-up.